Recent Advances in Radical Difunctionalization of Simple Alkenes - Lan, Xing‐Wang; Wang, Nai‐Xing; Xing, Yalan (European journal of organic chemistry, 2017)
Direct difunctionalization of simple alkenes, the incorporation of two functional groups onto a carbon–carbon double bond, is of particular interest to the chemical community owing to its important applications in organic synthesis. Mechanistically, two types of reactions – metal‐catalyzed nucleophilic difunctionalization and radical difunctionalization – dominate this research field. Radical difunctionalization is more appealing from a synthetic perspective than metal‐catalyzed nucleophilic difunctionalization because it allows the conversion of simple alkenes into complex molecules in a rapid and convenient manner. Furthermore, radical difunctionalization allows addition to simple alkenes by various carbon‐centered radicals and even heteroatom‐centered radicals. This review gives an overview of intermolecular and intramolecular radical difunctionalization of simple alkenes, with an emphasis on the reaction patterns and mechanisms, as well as potential applications in synthetic chemistry. Radical difunctionalization of simple alkenes, incorporating two functional groups onto a carbon–carbon double bond, is a fascinating methodology for increasing molecular complexity. This has been a rapidly developing area, especially in the last three years. This microreview collects recent advances and provides synthetic methods, catalytic systems, and reaction mechanisms.